Transpolitanism, Mobilities and Appropriation: Dancing Salsa in West Africa (Benin/Ghana) - (:unkn) unknown (My University, 2019)
In West Africa, many salsa festivals have emerged in the past recent years. Based on ethnographic research conducted in Benin and Ghana, this article offers a comparative anthropology of the appropriation processes of salsa in Cotonou and Accra. By analyzing the circulation networks created by the practice of salsa between neighboring countries in the light of “transpolitanism”, the article shows how the transnationalization of salsa is transformed by its subsequent translocalization into the metropolises of the Gulf of Benin.‪
Keywords: African Research